Circunferencia de la cintura como predictor de factores de riesgo de enfermedad cardiovascular en residentes costarricenses de 60 años y más - Aguilar Fernández, Eduardo (2021)
“Waist circumference as a predictor of cardiovascular disease risk factors in Costa Rican residents aged 60 years and over”. Introduction: There is a negative effect of abdominal obesity on the health of older adults. Objective: To investigate the relationship between waist circumference (WC) and metabolic risk factors associated with cardiovascular disease in this population. Methods: A population cross-sectional study with a total of 2 418 people of the project Costa Rica: Longevity and Healthy Aging Study and referred to as CRELES. Spearman´s correlation coefficient was calculated to estimate the correlations between WC with different risk factors for cardiovascular disease. Logistic regression analyses to calculate the odds ratio of a person presenting a cardiovascular risk factor according to the different WC levels. Results: People with wider waists are at greater risk of low HDL cholesterol, high triglycerides, diabetes and hypertension. In men, the strongest correlation was with triglycerides (r = 0,345), and in women with glycosylated hemoglobin (r = 0,262). Conclusions: Waist size can predict some risk factors for cardiovascular disease in Costa Rican residents aged 60 years and over.